The Impact of uncertainty spillover on cash holdings behavior of Turkish firms - TAN, ÖMER FARUK; AKSOY HAZIR, ÇAĞRI (My University, 2022)
This paper examines the impact of the World Uncertainty Spillover IndexUnited States (WUSI-USA) on cash holdings policy of 211 Turkish firms between 2005 and 2019, applying unbalanced panel data regression strategy. According to the findings, a positive relationship exists between uncertainty spillovers and cash holdings. When faced with uncertainty, firms prefer to restrain cash reserves for a precautionary motive. From the real options perspective, firms delay or postpone their investments under uncertain conditions. In addition, dividend payments, cash flow, tangibility, non-cash working capital, short-term debt, and capital expenditure are major determinants of cash holdings. Finally, under alternative models, we find robust results.
Keywords: Sosyal ve Beşeri Bilimler; Finans Ekonomisi; Social Sciences and Humanities; Financial Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; Cash holding; World uncertainty spillovers index; Turkey; Panel data